The landscape of accessible chromatin in quiescent cardiac fibroblasts and cardiac fibroblasts activated after myocardial infarction. Issue 9 (2nd September 2022) - Li, Chaoyang; Sun, Jiangwen; Liu, Qianglin; Dodlapati, Sanjeeva; Ming, Hao; Wang, Leshan; Li, Yuxia; Li, Rui; Jiang, Zongliang; Francis, Joseph; Fu, Xing
ABSTRACT: After myocardial infarction, the massive death of cardiomyocytes leads to cardiac fibroblast proliferation and myofibroblast differentiation, which contributes to the extracellular matrix remodelling of the infarcted myocardium. We recently found that myofibroblasts further differentiate into matrifibrocytes, a newly identified cardiac fibroblast differentiation state. Cardiac fibroblasts of different states have distinct gene expression profiles closely related to their functions. However, the mechanism responsible for the gene expression changes during these activation and differentiation events is still not clear. In this study, the gene expression profiling and genome-wide accessible chromatin mapping of mouse cardiac fibroblasts isolated from the uninjured myocardium and the infarct at multiple time points corresponding to different differentiation states were performed by RNA sequencing (RNA-seq) and the assay for transposase-accessible chromatin with high-throughput sequencing (ATAC-seq), respectively. ATAC-seq peaks were highly enriched in the promoter area and the distal area where the enhancers are located. A positive correlation was identified between the expression and promoter accessibility for many dynamically expressed genes, even though evidence showed that mechanisms independent of chromatin accessibility may also contribute to the gene expression changes in cardiac fibroblasts after MI. Moreover, motif enrichment analysis and gene regulatory network construction identified transcription factors that possibly contributed to the differential gene expression between cardiac fibroblasts of different states.